Internalizing Tazkiyatun Nafs as an Effort to Address Gadget Addiction - Maria Ulfa; Ekawati, Ekawati (Penerbit Hellow Pustaka, 2026)
This article aims to explain the concept of tazkiyatun nafs, proposed by Imam Al Gazali, as an effort to treat gadget addiction. This discussion focuses on explaining the meaning of gadget addiction, the meaning of tazkiyatun nafs, its stages, and their relevance to overcoming gadget addiction. The research method used was library research. Data was extracted from books, Quranic verses, hadith texts, and journals that explain gadget addiction and the concept of tazkiyatun nafs. The findings of this study indicate that gadgets are small devices that have significant benefits in assisting human work. However, excessive gadget use can lead to addiction and cause a person to neglect their obligations due to excessive focus on their gadget. Through the concept of tazkiyatun nafs, proposed by Imam Al Gazali, a person can overcome their dependence on gadgets by implementing the stages of takhalli, tahalli, and tajalli.